Employing the natural symbol of the revolutionary personality of Ibrahim Ahmed - دكجؤر عبداهلل ًاسٌي ئاوٌَدى; واوۆسجاى ًارًدەدەر حًٍدەر جٍوٍَر ئٍحىٍد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is no doubt that the symbol covers a wide space in the world literature and Kurdish literature modern and contemporary, and has a relationship with poetic poetic creativity. This research, which is characterized by the use of the natural symbol of the revolutionary personality of Ibrahim Ahmed, deals with the status of nature, since ancient times, in poets. The poets mentioned the elements of nature in their poems, Between symbol and nature, and used the symbol of multiple meanings, so nature was treated by poets as a symbolic inspiration enriched by their poetic experiences. Ibrahim Ahmed is one of the great Kurdish poets who have benefited from nature in using it symbols in his poems to express the revolutionary personality and displayed wonderful poetic images through it.